PROTOCOL: Effects of guaranteed basic income interventions on poverty‐related outcomes in high‐income countries: A systematic review. Issue 4 (6th October 2022) - Rizvi, Anita; Welch, Vivian; Gibson, Marcia; Labelle, Patrick R.; Pollard, Christina; Wells, George A.; Kristjansson, Elizabeth
Abstract: This is the protocol for a Campbell systematic review. The objectives are as follows: to appraise and synthesize the available quantitative evidence on GBI interventions in high‐income countries, for the purpose of comparing the relative effectiveness of specific forms of GBI for alleviating poverty.